2018
DOI: 10.1111/oik.05571
|View full text |Cite
|
Sign up to set email alerts
|

Trait patterns across space and time suggest an interplay of facilitation and competition acting on Neotropical hummingbird‐pollinated plant communities

Abstract: Pollinators may influence plant community assembly through biotic filtering and/or plant–plant competition and facilitation. The relative importance of each process, however, vary according to the scale and how strongly plants share their pollinators, and possibly in relation to the pollinator groups considered. We here investigated the assembly of three Atlantic forest hummingbird‐pollinated plant communities across space (among all species in the communities) and time, i.e. yearly flowering phenology (betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 53 publications
(106 reference statements)
11
29
0
Order By: Relevance
“…Hummingbird-pollinated plants experienced facilitation and competition in similar proportions. Previous studies suggested an interplay of facilitation and competition on hummingbird-pollinated plant communities Bergamo et al 2018), and our results confirm that both interaction signs are similarly important for these plants. CONCLUSION Pollination success was greatest when a plant was rare on a landscape scale but occurred in locally dense patches of conspecific or heterospecific flowers.…”
Section: Determinants Of Landscape and Plot Density-dependencesupporting
confidence: 89%
“…Hummingbird-pollinated plants experienced facilitation and competition in similar proportions. Previous studies suggested an interplay of facilitation and competition on hummingbird-pollinated plant communities Bergamo et al 2018), and our results confirm that both interaction signs are similarly important for these plants. CONCLUSION Pollination success was greatest when a plant was rare on a landscape scale but occurred in locally dense patches of conspecific or heterospecific flowers.…”
Section: Determinants Of Landscape and Plot Density-dependencesupporting
confidence: 89%
“…Desaegher et al (2018) showed that floral visitors of insect families that had a preference for nontubular corollas (generally insects with small mouthparts and considered as specialists) were rare in urbanized areas of the Île-de-France region (see also Geslin, Gauzens, Thébault, & Dajoz, 2013). In different contexts, two recent community-level studies (Bergamo, Wolowski, Maruyama, Vizentin-Bugoni, & Sazima, 2018;Fantinato, Del Vecchio, Giovanetti, Acosta, & Buffa, 2018) suggested complex interplay of facilitation and competition processes among flowering plants through pollination by insects. In different contexts, two recent community-level studies (Bergamo, Wolowski, Maruyama, Vizentin-Bugoni, & Sazima, 2018;Fantinato, Del Vecchio, Giovanetti, Acosta, & Buffa, 2018) suggested complex interplay of facilitation and competition processes among flowering plants through pollination by insects.…”
Section: Introductionmentioning
confidence: 99%
“…In different contexts, two recent community-level studies (Bergamo, Wolowski, Maruyama, Vizentin-Bugoni, & Sazima, 2018;Fantinato, Del Vecchio, Giovanetti, Acosta, & Buffa, 2018) suggested complex interplay of facilitation and competition processes among flowering plants through pollination by insects. This differentiation may allow different pollen placement on pollinator bodies, which can reduce competition among plant species and increase effective pollination (Bergamo et al, 2018;Fantinato et al, 2018). These studies also showed that coflowering, pollinator-sharing species tended to differ in another position in the corollas.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations